Pemaknaan Ibadah Live Streaming Berdasarkan Fenomenologi Edmund Husserl - Johana Ruadjanna Tangirerung; Kristanto Kristanto (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Abstract. This study aimed to find the meaning of worship, fellowship and liturgy experienced by the congregation during Sunday Worship live streaming during the Covid-19 pandemic. The method used was descriptive qualitative phenomenological Edmund Husserl, which explains the meaning or meaning of a life experience of several people, groups of a concept, habit or phenomenon. This study found that the congregation was less able to experience the meaning of live streaming worship related to the meaning of fellowship, worship and liturgy during the Covid-19 pandemic, because they did not understand its essence. The true meaning of worship can be experienced when understanding worship as fellowship with the Triune God who transcends time and space.Abstrak. Penelitian ini bertujuan menemukan makna ibadah, persekutuan dan liturgi yang dialami jemaat dalam Ibadah Minggu secara live streaming pada masa pandemi Covid-19. Metode yang digunakan adalah kualitatif deskriptif fenomenologis Edmund Husserl, yang menjelaskan arti atau makna sebuah pengalaman hidup beberapa orang, kelompok atas sebuah konsep, kebiasaan atau fenomena. Penelitian ini menemukan bahwa jemaat kurang dapat mengalami makna ibadah live streaming terkait makna persekutuan, ibadah maupun liturgi pada masa pandemi Covid-19, karena kurang memahami esensinya. Makna ibadah yang sesungguhnya dapat dirasakan apabila memahami ibadah sebagai persekutuan dengan Allah Tritunggal yang melampaui urang dan waktu.